1976
DOI: 10.1073/pnas.73.6.1989
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic transformation of clonal myogenic cells to cells resembling chondrocytes.

Abstract: The nicotinamide analogue 6-aminonicotinamide and dibutyryl 3':5'-cAMP inhibit myogenesis in a clonal rat cell line from skeletal muscle. Both reagents produce a similar morphological response in the cells, and stimulate collagen and glycosaminoglycan synthesis. These data suggest that 6-aminonicotinamide and dibutyryl cAMP induce a phenotypic transformation of myogenic ceNls to cells that share many characteristics with chondrocytes. Clonal skeletal muscle myogenic cell lines divide as mononucleate cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Cholesterol (1 mg/ml), N,N'-hexamethylenebisacetamide (HMBA, 9 mM), and methylamine (5 mM)were purchased from Nakalai Tesque (Kyoto, Japan). Lysolecithin (150 //g/ml), trifluoper- 32,38,39,42,43,46,47). Onthe other hand, it has been suggested that there are some differences between avian and mammalian myogenic differentiation (15, 40), hence we first examined whether or not these inhibitors block the fusion of QM-RSV cells at 41°C.…”
Section: Methodsmentioning
confidence: 99%
“…Cholesterol (1 mg/ml), N,N'-hexamethylenebisacetamide (HMBA, 9 mM), and methylamine (5 mM)were purchased from Nakalai Tesque (Kyoto, Japan). Lysolecithin (150 //g/ml), trifluoper- 32,38,39,42,43,46,47). Onthe other hand, it has been suggested that there are some differences between avian and mammalian myogenic differentiation (15, 40), hence we first examined whether or not these inhibitors block the fusion of QM-RSV cells at 41°C.…”
Section: Methodsmentioning
confidence: 99%